HOUSEHOLD ACCESSIBILITY TO STAPLE FOOD AND FACTORS AFFECTING IN RIAU PROVINCE, INDONESIA - Gevisioner , Rudi Febriamansyah , Ifdal, Suardi Tarumun (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Accessibility of the community to food is an absolute requirement to achieve community welfare. Food insecurity is a reflection of the people being unable to access food. This study aimed to determine the factors that affected food accessibility to fulfill food needs in Riau Province. The research approach was a survey. This research used SEM-Smart Partial Least Square (Smart PLS) analysis tool. The results showed that the factors of the level of economic, physical, social, and food culture together affected the level of household food accessibility in Riau province by 55.4 percent. The level of economic capability, physical availability, and social ability had a positive and significant effect on the level of food accessibility. In contrast, the level of food culture had a negative and significant impact on the level of household accessibility to food.